2020
DOI: 10.1016/j.neurobiolaging.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma YKL-40 with brain amyloid-β levels, memory performance, and sex in subjective memory complainers

Abstract: Neuroinflammation, a key early pathomechanistic alteration of Alzheimer's disease, may represent either a detrimental or a compensatory mechanism or both (according to the disease stage). YKL-40, a glycoprotein highly expressed in differentiated glial cells, is a candidate biomarker for in vivo tracking neuroinflammation in humans. We performed a longitudinal study in a monocentric cohort of cognitively healthy individuals at risk for Alzheimer's disease exploring whether age, sex, and the apolipoprotein E ε4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
(47 reference statements)
2
17
2
Order By: Relevance
“…YKL-40, also known as chitinase-3-like protein 1 (CHI3L1), is a pro-inflammatory glycoprotein expressed in differentiated glial cells, and is considered a marker of neuroinflammation [ 81 , 82 ]. Recently, serum levels of YKL-40 have been shown to be a promising marker for early MCI diagnosis and patient selection, as it is capable of discriminating between cognitive normality and mild cognitive impairment with 85% sensitivity and specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…YKL-40, also known as chitinase-3-like protein 1 (CHI3L1), is a pro-inflammatory glycoprotein expressed in differentiated glial cells, and is considered a marker of neuroinflammation [ 81 , 82 ]. Recently, serum levels of YKL-40 have been shown to be a promising marker for early MCI diagnosis and patient selection, as it is capable of discriminating between cognitive normality and mild cognitive impairment with 85% sensitivity and specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Results from a multicentre study have shown that plasma YKL-40 concentration is higher in AD-related dementia, similar to what has been observed with YKL-40 in the CSF [ 82 ]. However, it should be noted that high levels of blood YKL-40 have also been reported in aging, vascular dementia, frontotemporal dementia, sporadic Creutzfeldt–Jakob disease, and Lewy body dementia, as well as to vary according to sex, thus almost excluding its applicability as a specific and differential AD biomarker [ 81 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparable to GFAP, YKL-40 levels increase with age, in CSF, and also in plasma. When measured in plasma, higher plasma YKL-40 concentrations seem to be correlated with male sex, older age, APOE ε4 status, and cerebral accumulation of Aβ measured with PET [ 31 ]. Our sample did not find YKL-40 to be correlated with age, sex, APOE ε4 status and Aβ measured in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study has explicitly reported sex disaggregated data on the serum levels of YKL-40 in CKD or CVD populations. However, sex differences in plasma YKL-40 levels have been presented in studies assessing neuroinflammation conditions, such as Alzheimer's disease, where YKL-40 levels were found higher in males [59]. Whilst explicit sex differences in YKL-40 levels alone were not observed in our ESKD cohort, the sex-specific associations explored thereafter could give precedent to study YKL-40 further in a sex disaggregated approach including larger cohorts prospectively based on eGFR through CKD stages.…”
Section: Discussionmentioning
confidence: 70%